Analisis Peran Komite Keperawatan dalam Implementasi Kredensial Tenaga Keperawatan di RSUD Kota Dumai - Ria Agusnita; Budi Hartono; Abdurrahman Hamid; Hetty Ismainar; Lita Lita (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Based on the data obtained from the nursing committee, it was found that the credentialing process for nursing staff at the Dumai City Hospital has only been carried out on 1 (one) clinical nurse, the implementation of credentials for the level above has not been carried out. This is not in accordance with PMK Number 49 of 2013 and PMK Number 40 of 2017 which explains that the nursing committee has a central role in conducting the credentialing process for new nursing staff, re-credentialing in accordance with a predetermined time maximum once every 3 years. This study aims to analyze the role of the nursing committee in the implementation of nursing credentials in Dumai City Hospital. This research is a qualitative type with a RAP (Rapid Assessment Procedure) design which was carried out in May-July 2022. The key informants in this study were the Director of the Dumai City Hospital, the Main Informant, the chairman of the nursing committee, the credential subcommittee, bestari partners, nurses and supporting informants. head of nursing and secretary of the nursing committee. Data collection techniques used in-depth interviews, observation, document review and FGD which were processed by triangulation, and questionnaires were obtained using the Analytical Hierarchy Process (AHP) method. The results of the research found that out of 6 (six) there were 2 (two) committee roles that had not been optimally carried out, namely rearranging clinical authority and white papers and re-credentialing for old nursing staff.